CLINICAL CHARACTERISTIC OF ADULT PATIENTS WITH DENGUE HEMORRHAGIC FEVER AT PROF. DR. SULIANTI SAROSO SUNTER INFECTIOUS HOSPITAL 2018 - Rasyidah, Ghina; Anandani, Adinta (Muhammadiyah Medical Journal, 2020)
Background: Dengue is a viral disease transmitted by mosquito to humans and becomes a problem for the health of Indonesian people. Dengue Hemorrhagic Fever occurs due to several epidemiological factors. The purpose of this study is to determine the clinical characteristics of adult patients with Dengue Hemorrhagic Fever at Prof. dr. Sulianti Saroso Sunter Infectious Hospital 2018. Method: This Study was an observational descriptive study by taking medical record samples in 49 adult patients Dengue Hemorrhagic Fever in 2018. Results: From the 49 cases of Dengue Haemorrhagic Fever, the highest fender category was male (65,3%), occurred in the 18-25 year age category (38,8%), and the average patient worked as a Private Employee (55,1%). Most patients were hospitalized for the less than 7 days (83,7%). Clinical manifestations were fever (95,9%), nausea (85,7%) and headache (71,4%). Physical examination found was fever (100%) and hepatomegaly (12,2%). Laboratory tests showed normal hematocrit values (71,4%), thrombocytopenia values (87,8%), normal leukocyte values (49%), positive IgG serology tests (83,7%), IgM serology tests (71,4%), Positive IgM and IgG Serology test (69,3%), and NS1 Serology test (2%). Management provided is the administration of intravenous infus fluid drops (100%), PPI (87,8%), H2 Antagonist (4,1%), and Antipiretik (83,7%). The outcome patient is recovered and no complications were found. Conclusion: Dengue Hemorrhagic fever occurs in the age range of 18-25 years with dominant clinical characteristic of fever and thrombocytopenia. And, the most given treatment is Intravena Fluid therapy.